A cross-sectional study on the motion-induced dizziness and/or vertigo among Malaysian adults - Mohd Sakeri, Nurul Syarida; Zakaria, Mohd Normani; Salim, Rosdan; Wahat, Nor Haniza; Jamaluddin, Saiful Adli; Al- Hadeethi, Yahia F. Hussein (Nova Science Publishers, 2022)
Balance disorders are common in adults. In order to develop an effective vestibular rehabilitation method, specific profiles of balance disordered patients should be studied. Therefore, the aim of the present study was to explore the motion-related activities that trigger or worsen dizziness and/or vertigo among Malaysian adults. In this cross-sectional study, the medical records of 60 eligible participants were reviewed. They were then phone-interviewed to acquire information on the routine activities that triggered or worsened their vestibular symptoms. Of 60 respondents, 78.33% of them reported that head or body movements would trigger their dizziness and/or vertigo. The reported movements were looking up and/or down (63.8%), head turn to the left or right (17%), from sitting to standing up (14.9%), standing too long (12.8%), walking (6.4%), quick turning to the back (2.1%), and jumping (2.1%). Due to the motion-induced dizziness, 40% of respondents reported difficulties in driving and 18.3% had difficulties associated with sleeping. A high percentage of balance disordered adults had difficulties in pursuing their daily life activities as head and body movements would trigger or worsen their vestibular symptoms. Based on these findings, a more culturally specific vestibular rehabilitation technique can be developed for treating balance disorders among this population.